Detection of Snow Cover us ing NDSI and False Color Methods - Ghazal , Nawal k.; Shahbaz , Mustafa J. (Iraqi Journal of Science, 2021)
Snowfall is one of the most important natural phenomena that can be seen in thewinter which is considered as a rare phenomenon in the Middle East. Snow iscovering parts of mountains in northern Iraq and neighboring countries in the firstmonths of the year. In this research, the snow cover can be detected and monitoredusing pseudo color method, and the Normalized Difference Snow INDECES(NDSI). Snow cover is difficult to detect in true color satellite images because thewhite color of snow cover is the same color with the cloud cover. Modis sensors thatcarried by Terra and Equa satellites images have been used in different bands anddifferent resolution and the case studied in 4/2/2017, 5/2/2017.